Translation Method of Metaphorical Speech in Dead Poets Society Movie: A Qualitative Analysis: Metode Penerjemahan Ujaran Metafora dalam Film Dead Poets Society: Sebuah Analisis Kualitatif - Febrian, Hartini Diaz; Fediyanto, Niko (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to explore the method of translating metaphorical utterances in the Dead Poets Society movie, given the challenges metaphors pose in conveying meanings through comparisons. The research design adopts a qualitative approach, with data collected through direct observation, including watching, understanding, classifying, and analyzing 26 randomly selected metaphorical samples. The study reveals that semantic translation dominates the transmission of metaphorical meaning, with translators oriented towards the semantic and syntactic structure of the source language. Translators tend to employ word-for-word, literal, semantic, and faithful translation techniques. The implications of the findings suggest that semantic translation is more prevalent than communicative translation in conveying messages and meanings, with literal translation being the most widely used method. However, some sentences were left untranslated in the target language. This study provides valuable insights for translation studies, contributing to a better understanding of metaphor translation and its impact on communication in movie contexts. Highlight: Methodological Approach: The study adopts a qualitative research design to explore translation methods used in metaphorical utterances in the Dead Poets Society movie. Dominance of Semantic Translation: The analysis reveals that semantic translation is the primary approach employed by translators in conveying metaphorical meaning, emphasizing the importance of semantic and syntactic structure of the source language. Implications for Translation: The study highlights the prevalence of word-for-word, literal, semantic, and faithful translation methods, shedding light on the challenges of translating metaphors and their impact on conveying messages and meanings. Keyword: Translation Methods, Metaphorical Utterances, Dead Poets Society Movie, Semantic Translation, Qualitative Research